Karakteristik Perjanjian Asuransi Tanggung Gugat Profesi Dokter Terhadap Klaim Malapraktik Medis - Christine Elisia Widjaya; Dinar Kripsiaji; Zahry Vandawati Chumaida (Universitas Airlangga, 2023)
AbstractThis article examines the characteristics of the medical profession liability insurance agreement, which is a method to transfer the risk of medical liability (the insured) to the insurance company (the insurer). To discuss this, normative research methods are used. This study found that medical profession liability insurance is a long tail (injury or injury) which takes a few moments to find after a procedure or medical action is carried out, the dispute resolution process is quite long, and the assistance of the medicolegal team is needed in the claim investigation process). the amount of compensation paid is rather difficult to predict, the risk exposure and the amount of the premium varies in each specialization of medical practice, and there are difficulties in identifying and classifying specialties into classes (classes) accurately. The purpose of this insurance is to protect and maintain the reputation of doctors as a profession based on the trust given by patients and to restore the victim’s (patient’s) health condition. AbstrakArtikel ini mengkaji karakteristik perjanjian asuransi tanggung gugat profesi dokter, yaitu sebuah metode untuk mengalihkan risiko tanggung gugat dokter (Tertanggung) kepada perusahaan asuransi (Penanggung). Untuk membahas hal itu, digunakan metode penelitian normatif. Penelitian ini menemukan bahwa asuransi tanggung gugat profesi dokter bersifat long tail (luka atau cedera) yang dialami memerlukan waktu beberapa saat untuk ditemukan setelah suatu prosedur atau tindakan medis dilakukan, proses penyelesaian sengketa cukup lama, dan diperlukan bantuan tim medikolegal dalam proses investigasi klaim), jumlah pembayaran ganti kerugian yang agak sukar diprediksi, paparan risiko dan besaran premi yang bervariasi pada setiap spesialisasi praktik kedokteran, serta adanya kesulitan dalam mengenali dan mengelompokkan spesialisasi-spesialisasi dalam golongan (kelas) secara akurat. Tujuan asuransi ini adalah melindungi dan mempertahankan reputasi dokter sebagai profesi berlandaskan kepercayaan yang diberikan oleh pasien serta memulihkan kondisi kesehatan korban (pasien).